Pengaruh Pelatihan, Human Capital, dan Beban Kerja terhadap Kinerja Petugas SUSENAS 2024 di BPS Kota Pasuruan - Dinda Anggi Cipta Pratiwi; Vita Fibriyani; Eni Erwantiningsih (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The phenomenon underlying this research is the importance of statistical data quality in national and regional development planning, which is highly dependent on the accuracy and precision of field survey data. In this context, the performance of National Socioeconomic Survey (SUSENAS) officers is a crucial factor determining the quality of collected data. Therefore, this study aims to determine the effect of training, human capital, and workload on the performance of 2024 SUSENAS officers at the Central Statistics Agency (BPS) of Pasuruan City. This study uses a quantitative approach with a survey method. The population in this study were all 2024 SUSENAS field officers at BPS Pasuruan City, with a sample size of 37 people. Data collection techniques were carried out through the distribution of questionnaires compiled based on the indicators of each variable. The obtained data were analyzed using multiple linear regression methods to test the simultaneous and partial effects of the independent variables on the dependent variable. The results show that training, human capital, and workload simultaneously have a significant effect on the performance of SUSENAS officers. This is evidenced by the calculated F value of 23.514 which is greater than the F table of 2.891 and the significance value of 0.000 which is smaller than α = 0.05. The coefficient of determination (R²) value of 68.1% indicates that the three variables are able to explain the variation in officer performance by 68.1%, with the contribution of training of 24.3%, human capital 21.0%, and workload 22.8%. Partially, the three variables are also proven to have a significant effect on performance. Among the three, training is the most dominant variable with a beta coefficient value of 0.394 or contributing 39.4%. These findings are expected to be the basis for consideration for BPS Pasuruan City in formulating strategies to improve the performance of field officers.